2021
DOI: 10.3390/ijerph181910485
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Factors Moderating Changes in Tobacco Use Dependence Care Delivery Following a Comprehensive Tobacco-Free Workplace Intervention in Non-Profit Substance Use Treatment Centers

Abstract: Although tobacco use is the leading preventable cause of death and is elevated among patients with substance use disorders, many substance use treatment centers (SUTCs) do not offer tobacco use interventions (i.e., screening and treatment). This study examined a key outcome of the implementation of a tobacco-free workplace program that provided education and specialized training to employees; namely, changes in clinician provision of the five As (Asking about tobacco use; Advising to quit; Assessing willingnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 53 publications
(99 reference statements)
3
20
0
Order By: Relevance
“…However, although it is highly likely that these studies had different survey respondents, the results indicate that rates of tobacco screening in Texas’ mental health and substance abuse treatment centers have increased over time (i.e., from 58.4% and 70.2%, respectively, in 2016 [ 24 ] to 81.25% and 80%, respectively, in the current 2021 data collection). This could be the result of several known public health efforts in Texas geared toward improving tobacco use disorder care in behavioral health treatment settings (e.g., [ 50 , 51 , 52 , 53 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]). Regardless, tobacco screening should be occurring with 100% of adult patients in these settings, as well as in other health care settings where patients with behavioral health care needs are seen (like FQHCs), indicating the need for more progress in this area.…”
Section: Discussionmentioning
confidence: 99%
“…However, although it is highly likely that these studies had different survey respondents, the results indicate that rates of tobacco screening in Texas’ mental health and substance abuse treatment centers have increased over time (i.e., from 58.4% and 70.2%, respectively, in 2016 [ 24 ] to 81.25% and 80%, respectively, in the current 2021 data collection). This could be the result of several known public health efforts in Texas geared toward improving tobacco use disorder care in behavioral health treatment settings (e.g., [ 50 , 51 , 52 , 53 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ]). Regardless, tobacco screening should be occurring with 100% of adult patients in these settings, as well as in other health care settings where patients with behavioral health care needs are seen (like FQHCs), indicating the need for more progress in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco use is exceedingly high among individuals receiving care for OUD, but rarely addressed by clinicians in these treatment settings [ 9 , 10 , 11 ]. Although prior studies implemented a similar program in addiction/substance use treatment centers [ 25 , 31 , 35 , 43 , 44 , 45 , 46 ], to our knowledge, no prior studies have reported details of the implementation of multi-component, multi-level treatment programs designed to build capacity for addressing tobacco use within OUD treatment centers. The current study addressed this gap by describing outcomes of the implementation of TTTF, a comprehensive tobacco-free workplace program [ 24 , 25 , 26 , 27 , 28 , 30 , 32 ], within 7 OUD treatment centers in Texas.…”
Section: Discussionmentioning
confidence: 99%
“…The TTTF program includes adoption of a 100% tobacco-free workplace policy that covers all tobacco products, including electronic nicotine delivery systems, as well as implementing tobacco use screenings that assess clients for use of these products. To date, TTTF has partnered with 23 local mental health authorities (LMHAs) in the implementation of this comprehensive tobacco-free workplace program [22,47,54,[56][57][58]. LMHAs are non-profit, state-funded agencies throughout Texas responsible for providing behavioral health services through community mental health centers within a safety-net healthcare system that serves underserved, lower-income individuals [59].…”
Section: Tttf Train-the-trainermentioning
confidence: 99%
“…LMHAs are non-profit, state-funded agencies throughout Texas responsible for providing behavioral health services through community mental health centers within a safety-net healthcare system that serves underserved, lower-income individuals [59]. While provision of general employee and specialized provider tobacco education has been a cornerstone of the TTTF program that has successfully increased provider delivery of tobacco cessation services to clients [58], the effects of the education were continuously being lost due to high employee turnover [60,61]. The TTTF Train-the-Trainer program was developed to embed sustainable, local expertise within LMHAs on the general harms of tobacco use and how to treat tobacco dependence using evidence-based tobacco cessation interventions [18].…”
Section: Tttf Train-the-trainermentioning
confidence: 99%